2018
DOI: 10.1080/00913847.2018.1427412
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mental health conditions in incoming division I collegiate athletes

Abstract: The lifetime prevalence of mental health conditions in this population (14.0%) is far less than estimates in the general population. This observation may be due to a combination of factors including exercise/athletic participation mitigating depressive symptoms, competitive selection, and underreporting. History of a mental health condition may be associated with injury, although causation cannot be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…Among female elite athletes, mental health disorders—especially eating disorders—are also prevalent 20–23. Among collegiate athletes, the prevalence of mental health disorders ranges from 10% to 25% for depression and eating disorders 24–30…”
Section: General Prevalence Of Mental Health Symptoms and Disorders Imentioning
confidence: 99%
“…Among female elite athletes, mental health disorders—especially eating disorders—are also prevalent 20–23. Among collegiate athletes, the prevalence of mental health disorders ranges from 10% to 25% for depression and eating disorders 24–30…”
Section: General Prevalence Of Mental Health Symptoms and Disorders Imentioning
confidence: 99%
“…[13] A research by Sarac et al conducted among American college athletes showed that the lifetime occurrence of mental health conditions in this population (14.0%) is far less lower than estimates in the general population. [14] In the analysis, the lowest percentage of dental students with major depressive disorder was found among those, who declared that they participated in social gatherings often enough. According to Elmer and Stadtfeld, individuals with symptoms of depression are more likely to be isolated in their social networks, which can lead to worsening of their symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Physical condition is the main factor for an athlete, especially a football athlete, and this factor must be passed by a football athlete before getting to know or train about technique, tactics and mentality. With this, a technique is needed [38]. Seeing that this factor is very important, it is necessary to use effective and efficient training techniques and models to improve the physical condition of soccer athletes, and one of the training models used in this study is circuit training [39].…”
Section: Discussionmentioning
confidence: 99%